Analisis Strategi Pemberdayaan Nelayan di Kecamatan Wedung Kabupaten Demak - Richa Amalia; Nurdien Harry Kistanto; Riris Tiani (Prodi Antropologi Fakultas Ilmu Budaya Universitas Diponegoro, 2021)
People in Wedung subdistrict are mostly search-eyed as fishermen with a total of 9,986 people. All fishermen in Bonang Sub-district are members of the Joint Venture Group (KUB). Fishermen in Wedung sub-district still use traditional fishing equipment and use small boats with a capacity of 1 to 4 people for fishing activities. The catch of marine fisheries both in Wedung subdistrict and in other sub-districts in Demak regency can only be auctioned at the Fish Auction Site (TPI). In addition to the KUB that was built directly by the Department of Marine Affairs and Fisheries Demak Regency also initiated the Business Incubator Mina Sejahtera to accompany and provide training to MSMEs processed fish by the fishing community. The funding provided through several empowerment programs in the form of KUB and Business Incubator implemented is considered not appropriate. In addition, the uncertain condition of fishermen and the absence of collateral make it difficult for them to obtain capital loans. The data used in this study is primary data obtained from interviews with key informants which are then compiled into strategy evaluation of Joint Venture Group and Business Incubator activities programs along with alternative aspects of fishermen empowerment program strategy. Based on the results of interviews with key persons, five aspects and thirteen alternatives were formulated for the strategy of empowering the fishing community in Wedung Sub-district. Alternative aspects of the strategy of empowering fishing communities in Wedung sub-district are: Economic Aspects, Social Aspects, Technology Aspects, Environmental Aspects and Institutional Aspects. Evaluation of the KUB activity program is the lack of assistance in the establishment of KUB administratively so that the formation of KUB often encounters constraints on the administrative process. Mina Sejahtera Business Incubator in organizing its program is not maximal and has not been able to adapt to digitalization, as a result of which UMKM are shaded less able to develop in marketing. As for the alternative aspects of fishermen empowerment strategy in Wedung Sub-district are: Direct assistance in the form of tools, direct assistance in the form of funds, Development of capital access, Socialization and training of fishery resource processing business, Improving socialization of knowledge and skills about fishery management towards the preservation of fishery resources.